Відкритий політичний світ — прихований демократичний етос - Богачов, А. (Інститут філософії ім. Г.С. Сковороди НАН України, 2009)
Plato's formula of the domination of intellect in society implies that only those who have and use true knowledge of the common good should actively participate in rational politics. Now Plato's formula legitimizes authorities that rely entirely on expert knowledge. Critics of «open society's enemies» often assume that the domination of the intellect is a matter of public governing. The author calls this equality of the intellect's authority and publicity «Habermas' formula», since the interpretation of the openness of the democratic world as the publicity of the intellect is attributed to this thinker. This article explores the connection between Plato's and Habermas' formulas to ultimately show the reasons why philosophy of intellectual domination fails to fully explain the openness of democracy as a just world. The author uses some ideas of the phenomenology of the political world that has been proposed by K. Held. The main proposition is as follows: a democratic society cannot be open if its democratic ethos isn't hidden; justice arises from the unity of openness and hiddenness, that is, it is not a product of intellectual arguments. There isn't any reason to attenuate this proposition with Held's idea of the world ethos. In this paper the author focuses on the ineluctability of the personal and lingual cultural horizon for political arguments.